Madhyarātera Bāṅalā Deśa, '71 theke '81 - Rasula, Iphatekhāra (Nasāsa, 1982)
Articles on the assissination of Sheikh Mujibur Rahman, 1922-1975, and Ziaur Rahman, 1936-1981, former presidents of Bangladesh.